Mysteries of Eigenvalues, Eigenvectors & their Applications in the Diagonalization of a Matrix & in the Cayley-Hamilton Theorem to Find the Matrix Inverse - Baral, Kamalmani (Journal of the Institute of Engineering, 2011)
In this paper we deal with eigenvalues and eigenvectors (E-values & E-vectors) in diagonalizating a square matrix and in the Cayley-Hamilton theorem used to find the inverse of a given square matrix. Key Words: Mysteries of Eigenvalues; Diagonalization of a Matrix; square matrix DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5116 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 237-242 Uploaded Date: 20 July, 2011